First detection of feline bocaparvovirus 2 and feline chaphamaparvovirus in healthy cats in Turkey - Abayli, Hasan; Can-Sahna, Kezban (Springer, 2022)
The pet cat's population and the number of viruses that infect them are increasing worldwide. Recently, feline chaphamaparvovirus (FeChPV, also called fechavirus) and feline bocaparvovirus (FBoV) infections, which are novel parvovirus species, have been reported in cats from different geographic regions. Here, we investigated FBoV 1-3 and FeChPVs in healthy cats in Turkey using PCR, where nuclear phosphoprotein 1 (NP1) is targeted for FBoV and NP for FeChPV. For this purpose, oropharygeal swabs were obtained from 70 healthy cats with different housing status from June 15 to December 1, 2020. After PCR screening tests, six out of 70 cats (5/47 shelter cats; 1/23 domestic cats) were found to be positive for FBOV, while two were positive for FeChPV (1/47 shelter cats; 1/23 domestic cats). No cat was found in which both viruses were detected. The nucleotide (nt) sequence comparison in the 310 base pair (bp) NP gene of the two FeChPVs identified in this study shared a high identity with each other (95.0% nt and 99% aa identities) and with previously reported FeChPVs (92.4-97.1% nt and 98.1-99.0% aa identities), including 313R/2019/ITA, 49E/2019/ITA, VRI_849, 284R/2019/ITA, and IDEXX-1. Here, the near-full length (1489 nt, 495 amino acids-aa) of the VP2 gene of the FechaV/Tur-2020/68 isolate obtained from the study was also sequenced. The nt and aa identity ratio of this isolate with other FeChPVs was 98.0-98.5%-96-96.5%, respectively. Sequences of the 465 bp NP1 gene of the six Turkish FBoV strains shared high identities with each other (99.6-100% nt and 99.3-100% aa identities) and with those of FBoV-2 strains (97.8-99.1% nt and 98.0-100% aa identities), including 16SY0701, 17CC0505-BoV2, HFXA-6, and POR1. All FBoVs detected in this study were classified as genotype 2, similar to the study conducted in Japan and Portugal. Here, the NS1 (partial), NP1, VP1 and VP2 gene of the FBoV-2/TUR/2020-14 strain obtained from the study were also sequenced and the nt and aa sequences showed high identities to the above-mentioned FBoV-2 strain/isolates (> 96%, except for the aa ratio of strain 16SY0701). In conclusion, this study shows that FBoV and FeChPV are present in healthy cats in Turkey, and these viruses can be detected from oropharyngeal swabs. Our findings contribute to further investigation of the prevalence, genotype distribution, and genetic diversity of Turkish FBoVs and FeChPVs, adding to the molecular epidemiology of FBoV and FeChPVs worldwide.
Keywords: Cats; FBoV-2; FeChPV; PCR; Turkey